First insights into the ISM at z > 8 with JWST: possible physical implications of a high [O iii] λ4363/[O iii] λ5007. Issue 1 (20th September 2022) - Katz, Harley; Saxena, Aayush; Cameron, Alex J; Carniani, Stefano; Bunker, Andrew J; Arribas, Santiago; Bhatawdekar, Rachana; Bowler, Rebecca A A; Boyett, Kristan N K; Cresci, Giovanni; Curtis-Lake, Emma; D'Eugenio, Francesco; et al.
ABSTRACT: We present a detailed analysis of the rest-frame optical emission line ratios for three spectroscopically confirmed galaxies at z > 7.5. The galaxies were identified in the James Webb Space Telescope ( JWST ) Early Release Observations field SMACS J0723.3 − 7327. By quantitatively comparing Balmer and oxygen line ratios of these galaxies with various low-redshift 'analogue' populations (e.g. Green Peas, Blueberries, etc.), we show that no single analogue population captures the diversity of line ratios of all three galaxies observed at z > 7.5. We find that S06355 at z  = 7.67 and S10612 at z  = 7.66 are similar to local Green Peas and Blueberries. In contrast, S04590 at z  = 8.50 appears to be significantly different from the other two galaxies, most resembling extremely low-metallicity systems in the local Universe. Perhaps the most striking spectral feature in S04590 is the curiously high [O iii ] λ4363/[O iii ] λ5007 ratio (RO3) of 0.048 (or 0.055 when dust-corrected), implying either extremely high electron temperatures, >3 × 10 4  K, or gas densities >10 4 cm −3 . Observed line ratios indicate that this galaxy is unlikely to host an AGN. Using photoionization modelling, we show that the inclusion of high-mass X-ray binaries or a high cosmic ray background in addition to a young, low-metallicity stellar population can provide the additional heating necessary to explain the observed high RO3 while remaining consistent with other observed line ratios. Our models represent a first step at accurately characterizing the dominant sources of photoionization and heating at very high redshifts, demonstrating that non-thermal processes may become important as we probe deeper into the Epoch of Reionization.